The Relationship of Age, Parity and Body Mass Index as Risk Factors to the Incidence of Uterine Myoma in Dr. Hasan Sadikin General Hospital - Ilma, Nurul; Tjahyadi, Dian; Judistiani, Tina Dewi (Althea Medical Journal, 2015)
Background: Uterine myoma is a benign gynecological tumor which is commonly occurred in women. The incidence of uterine myoma in the world is 20â35% while in Indonesia is about 2.4â11.7%. Age, parity, and body mass index are correlated with the incidence of uterine myoma. This study aimed to determine the relationship among those factors towards uterine myoma, and to identify the prognostic value of body mass index in order to prevent uterine myoma.Methods: A case-control study was conducted to examine 394 medical records of patients with uterine myoma at Department of Obstetrics and Gynecology Dr. Hasan Sadikin General Hospital Bandung from 2006 to 2011.Â The case group were 133 and the control group were 261. The data were the subjectâs weight, height, age, and parity. The correlation among all variable and the occurrence of uterine myomas were conducted using multiple logistic regression analysis.Results: There was no different range of age between the two groups. The incidence rate ratio of parity was 2.254 (95% confidence interval:1.310â3.876), followed by body mass index>33.0 incidence rate ratio was 1.691 (95% confidence interval: 0.477â5.994). From the receiver operating characteristic curve, it could be seen that the cut-off points for body mass index was 20.44 kg/mÂ², and the risk of uterine myomas scaled up as the increase of body mass index.Conclusions: Parity and BMI can affect the risk of uterine myomas. To prevent the incident of uterine myomas, parity must be limited and BMI must be below the cut-off points (20.44 kg/mÂ²).Â DOI:Â 10.15850/amj.v2n3.485